The Development of E-Learning Based Student Worksheets in the Basics of Da'wah Management Course - Emi Puspita Dewi; Dalinur M Nur; Jawasi Jawasi; Rizki Tsaniah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study attempts to create student worksheets for the Basics of Da’wah Management. This research falls under the category of development research. This study will create educational resources in the form of student worksheets that are legitimate, practical, and effective. The process will involve two stages: preliminary study and formative study. The preliminary stage involves planning and design, while the formative study stage covers Self Evaluation, Expert Reviews, One to One, Small Group, and Field Test with a sample of 20 semester 2 students. The findings indicate that the e-learning Student Worksheet is legitimate, practical, and successful in enhancing student comprehension of the Basics of Da’wah Management Course. 85% of students fall into the full group based on the results of student learning exams during the field test stage. The created LKM also garnered a favourable reaction from pupils who exhibited increased motivation to learn.